2023
DOI: 10.1038/s41593-023-01396-3
|View full text |Cite|
|
Sign up to set email alerts
|

Pedunculopontine Chx10+ neurons control global motor arrest in mice

Abstract: Arrest of ongoing movements is an integral part of executing motor programs. Behavioral arrest may happen upon termination of a variety of goal-directed movements or as a global motor arrest either in the context of fear or in response to salient environmental cues. The neuronal circuits that bridge with the executive motor circuits to implement a global motor arrest are poorly understood. We report the discovery that the activation of glutamatergic Chx10-derived neurons in the pedunculopontine nucleus (PPN) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 72 publications
2
9
0
Order By: Relevance
“…Our results identify a population of glutamatergic neurons in the PPN that project to the SNr, control the locomotion by effective modulation of gait. A recent study has described a population of glutamatergic neurons in the PPN defined by expression of the transcription factor Chx10( 13 ). High frequency stimulation (40 Hz) of these neurons in the PPN resulted in motor arrest as well reduction of respiration and heart rate( 13 ) and suggested that these cells define a circuit for global motor arrest( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results identify a population of glutamatergic neurons in the PPN that project to the SNr, control the locomotion by effective modulation of gait. A recent study has described a population of glutamatergic neurons in the PPN defined by expression of the transcription factor Chx10( 13 ). High frequency stimulation (40 Hz) of these neurons in the PPN resulted in motor arrest as well reduction of respiration and heart rate( 13 ) and suggested that these cells define a circuit for global motor arrest( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has described a population of glutamatergic neurons in the PPN defined by expression of the transcription factor Chx10( 13 ). High frequency stimulation (40 Hz) of these neurons in the PPN resulted in motor arrest as well reduction of respiration and heart rate( 13 ) and suggested that these cells define a circuit for global motor arrest( 13 ). Low frequency stimulation was not tested, and the pathways that mediate changes in gait, respiration and heart rate were not examined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also seen for example, in rodents as a freezing behavior to a pain-conditioned response or looming threat 21 with an immediate need for silence and immobility. It was recently observed that a similar arrest of movement could be induced by optogenetic stimulation of a subset of glutamatergic neurons, the Chx10 cells 1,4 , in a nucleus in the caudal mesencephalon known as the PedunculoPontine Nucleus (PPN). Similar behavior was observed by stimulation of unidentified neurons in PPN both in mice 2 and rats 3 and reduced motor activity and long-lasting muscle tone in mice 22 and cats 23,24 .…”
mentioning
confidence: 95%